The epidemic of HIV and syphilis and the correlation with substance abuse among men who have sex with men in China: A systematic review and meta-analysis - Zhao, Tian; Chen, Guohong; Sun, Chengqing; Gong, Xiangdong; Li, Huiyong; Fu, Gengfeng (Frontiers in Public Health, 2023)
Background In China, the HIV/AIDS epidemic among men who have sex with men (MSM) has been expanding in recent years. Substance abuse in MSM was not well studied as the independent risk factor for HIV and syphilis infection and other sexually transmitted diseases. The present review aimed to determine the correlation between HIV/Syphilis infections and substance abuse and other sexual risk behaviors among MSM. Methods We conducted a comprehensive search of PubMed, Web of Science, Embase, Scopus, Chinese National Knowledge Infrastructure, Chinese Wanfang Data, and VIP Chinese Journal Database for relevant articles of quantitative studies published between 2010 and May 31, 2022. Meta-analysis was performed using R software. Pooled estimated of the association-odds ratio, with 95% confidence intervals were calculated using random-effects models stratified by study design. Q statistics and I2 were used to measure the heterogeneity. Results Our meta-analysis included 61,719 Chinese MSM from 52 eligible studies. The pooled HIV prevalence rate among substance-abusing MSM was 10.0% (95% CI = 0.08–0.13). Substance abusers were more likely to have a higher prevalence of HIV (OR = 1.59) and syphilis (OR = 1.48) infections than non-substance abusers. Substance abusers were also more likely to seek sexual partners through the internet or social media applications (OR = 1.63), engage in unprotected anal intercourse (UAI) (OR = 1.69), group sex (OR = 2.78), and engage in commercial intercourse (OR = 2.04) compared to non-users. Regarding testing behaviors, substance abusers had a higher proportion of HIV or STI testing in their lifetime (OR = 1.70) compared with non-substance abusers (p < 0.05). They were also more likely to have had more sexual partners (≥2; OR = 2.31) and more likely to have consumed alcohol (OR = 1.49) in the past 6 months. Conclusions Our study shows the correlation between substance abuse and HIV/Syphilis infection. Eliminating disparities in HIV/Syphilis infection among substance abusing men who have sex with men (MSM) can be achieved if the Chinese government and public health sectors could provide targeted knowledge popularization and diagnosis interventions among high-risk populations.